Role of STAT3 Expression in Thyroid Cancer: A Meta-Analysis and Systematic Review Based on the Chinese Population. (15th April 2022) - Liang, Ya-Nan; Zhang, Zuwang; Song, Ji; Yang, Fuwei; Yang, Pan
Abstract : Background . Signal transduction and activator of transcription 3 (STAT3) is an oncogene with transcriptional activity. In recent years, there have been several studies concerning the clinicopathological significance of the expression of the STAT3 protein in thyroid cancer. However, the results are still inconsistent. In this study, we conducted a meta-analysis to evaluate the relationship between the expression of STAT3 protein and thyroid cancer susceptibility and its clinicopathological characteristics. Methods . We searched the China National Knowledge Infrastructure (CNKI) database, Chinese Biomedical Literature Database (CBM), Chinese Scientific and Journal Database (VIP), Wanfang, PubMed, and EMBASE. The time frame of the publication search was from the establishment of each of the databases until December 2021. We performed a meta-analysis to quantitatively evaluate the relationship between the expression of the STAT3 protein in thyroid cancer and its clinicopathological characteristics. Results . A total of eight articles were included in the meta-analysis, covering 448 thyroid cancer patients and 227 controls. Results indicated that the expression of STAT3 protein in thyroid cancer tissue is highly expressed (OR = 14.41, 95% CI (6.94, 29.91), p < 0.001). Besides, we also discovered that STAT3 protein is negatively correlated with thyroid cancer tumor diameter and TNM stage (OR = 0.13, 95% CI (0.05, 0.33), p < 0.001; OR = 0.40, 95% CI (0.24, 0.67), p < 0.001) and positively correlated with lymph node metastasis (OR = 2.83, 95% CI (1.08, 7.46), p = 0.035). However, STAT3 expression is not related to gender (OR = 0.88, 95% CI (0.54, 1.44), p = 0.609), age (OR = 0.54, 95% CI (0.21, 1.36), p = 0.191), capsular invasion (OR = 2.98, 95% CI (0.23, 38.29), p = 0.403), or tumor multiplicity (OR = 0.25, 95% CI (0.003, 19.28), p = 0.533). Conclusions . This study reveals that STAT3 protein expression is significantly related to the susceptibility and clinicopathological characteristics of thyroid cancer. It also suggests that STAT3 may be a potential predictor of the clinical progression of thyroid cancer.